Atezolizumab-induced myasthenia gravis in metastatic hepatocellular carcinoma: a case report and literature review - Rajani Gubbala; Arumugam Ponnuswamy; Nikhileshwar C. Reddy; Sanath Kandem; Nikhil Pathi; Senthil J. Rajappa (European Journal of Case Reports in Internal Medicine, 2026)
Immune checkpoint inhibitors (ICIs) have transformed the management of advanced malignancies but are associated with immune-related adverse events (irAEs), including rare neurological complications. We report a case of a 60-year-old male with metastatic hepatocellular carcinoma who developed severe myasthenia gravis (MG) following treatment with atezolizumab and bevacizumab. The patient was diagnosed with multifocal hepatocellular carcinoma in April 2025 and initiated on combination therapy with atezolizumab (1200 mg) and bevacizumab (600 mg) in May 2025. Approximately 2 weeks after receiving the first treatment cycle, he developed progressive fatigability, breathlessness, and dysphagia. During hospitalization, he experienced acute respiratory deterioration leading to cardiac arrest, requiring successful resuscitation and intensive care support. Subsequently, he developed unexplained hypercapnic respiratory failure during ventilator weaning attempts. Neuroimaging and cerebrospinal fluid analysis were unremarkable. Repetitive nerve stimulation demonstrated a postsynaptic neuromuscular junction disorder, and serum acetylcholine receptor antibodies were positive. A diagnosis of ICI-induced MG was established. The patient was treated with intravenous immunoglobulin, corticosteroids, and pyridostigmine. Despite therapy, respiratory failure persisted, necessitating prolonged ventilator support. His clinical course was further complicated by myocarditis, demyelinating motor-sensory axonal polyradiculoneuropathy, and sepsis, and he ultimately succumbed to his illness. This case highlights the importance of early recognition and prompt management of neurological irAEs, particularly in patients presenting with unexplained respiratory failure after initiation of ICI therapy.